Medicine and religion in the life of an Ottoman sheikh - Ragab, Ahmed.
1 online resource.
Keywords: In 1768, Aohmad al-Damanhaurai became the rector (shaykh) of al-Azhar, which was one of the most authoritative and respected positions in the Ottoman Empire. He occupied this position until his death. Despite being a prolific author, whose writings are largely extant, al-Damanhaurai remains almost unknown, and much of his work awaits study and analysis. This book aims to shed light on al-Damanhaurai's diverse intellectual background, and that of and his contemporaries, building on and continuing the scholarship on the academic thought of the late Ottoman Empire. The book specifically investigates the intersection of medical and religious knowledge in Eighteenth-Century Egypt. It takes as its focus a manuscript on anatomy by al-Damanhaurai (d. 1778), entitled “The Clear Statement on the Science of Anatomy (al-qawl al-osaraioh fai ilm al-tashraioh),“. The book includes an edited translation of The Clear Statement, which is a well-known but unstudied and unpublished manuscript. It also provides a summary translation and analysis of al-Damanhaurai's own intellectual autobiography. As such, the book provides an important window into a period that remains deeply understudied and a topic that continues to cause debates and controversies. This study, therefore, will be of keen interest to scholars working on the “post-Classical“ Islamic world, as well as historians of religion, science, and medicine looking beyond Europe in the Early Modern period.